Management of Eka-Kushtha through Ayurveda (Shodhana and Shamana Chikitsa)- A Case Study - Rekha; Prakash, Gayathri M; Sood, Sanjeev (International Research Journal of Ayurveda & Yoga, 2022)
Introduction-Psoriasis is the most common dermatological, chronic inflammatory condition characterized by erythematous, sharply demarcated papules and rounded plaques, covered by silvery micaceous scale. The exact cause is unknown but is thought to be related to genetic and environmental factors that trigger on over production of epidermal cells. In Ayurveda, all skin diseases are considered under heading of Kushtha. There are 7 Maha kushtha and 11 Kshudra kushtha. Eka-Kushtha is one of the Kshudra kushtha with vata-kapha predominance and symptoms of Eka-kushtha are Aswedanam, Mahavastu, Matsyashakalopamam, Krishna aruna varna which can be correlated with Psoriasis. 2-3% of the total world population have Psoriasis and Prevalence of Psoriasis in India ranges from 0.44 to 2.8%. Psoriasis is characterized by remissions and relapses. Although it is difficult to cure, yet topical and systemic therapeutic regimens administered singly or in combination, Current treatment modalities have their own limitation and side effects and there is a need for safe and effective treatment for psoriasis, where Ayurveda plays an important role. The basic principles of Ayurvedic treatment are Shodhana, Shamana and Nidana parivarjana. Material & Method- Hence present study highlights, management of Eka-Kushtha through Shodhana and Shamana chikitsa and in Shodhana chikitsa, Virechana karma is preferred. Result: Here an effort was made to treat a 60 years old male patient having signs and symptoms of Eka-Kushtha since last 10 years and in this study initially Shodhana chikitsa was given followed by Shamana chikitsa. Conclusions: Patient has had the disease for the past ten years and has been treated by various doctors, but has not had good results, and the disease has recurred. However, excellent outcomes were reached in this case using the Shodhana technique and Shaman Chikitsa.